A study of induced delamination and failure in woven composite laminates subject to short-beam shear testing. (January 2019) - Espadas-Escalante, J.J.; Isaksson, P.
Highlights: Delamination onset of woven composite beams differ from the typical homogeneous assumption. Relative layer shifting affects the shear stress distribution along the thickness. Delamination and failure onset depend on layer shifting. Abstract: Failure in woven composite laminates subject to global shear load is studied. Laminates are manufactured, tested and analyzed using X-ray computed tomography, scanning electron microscopy and finite element models. It is found that the stress distribution along the thickness direction is dependent on the layer shifting that alters different yarn interactions, which in turn, affects delamination and failure onset. A suggested failure mechanism is in agreement with experimental observations.